Concept of Education Management: Positioning-Differentiation-Brand (PDB) for the Advancement of Islamic Education (Study at SMK Muhammadiyah 7 Gondanglegi, Malang) - Muhtadin, Muhtadin; Rosyada, Dede; Hakim, Lukmanul; Fahrudin, Adi (Technium Social Sciences Journal, 2022)
Educational progress is produced by a strategic and quality process. To produce educational progress, the concept of educational management is needed with the Positioning-Differentiation-Brand strategy. This study aims to formulate a theoretical model: 1) positioning strategy developed by SMK Muhammadiyah 7 Gondanglegi to improve school competitiveness 2) differentiation strategy by SMK Muhammadiyah 7 Gondanglegi so as to strengthen the attractiveness of new students 3) branding strategy at SMK Muhammadiyah 7 Gondanglegi to make it known easier and become the hope of society 4) management strategy and reconstruction of Positioning-Differentiation-Brand (PDB) SMK Muhammadiyah 7 Gondanglegi so as to achieve the success of graduates being accepted by the industry and achieving school progress. This study uses a qualitative phenomenological approach in order to give birth to a phenomenological model formulation. Data collection techniques used: 1) direct observation, 2) documentation study, and 3) in-depth interviews. Data analysis using data reduction, data presentation, and drawing conclusions. The validity and reliability of the research results are measured by four criteria: 1) Credibility, 2) Transfermability, 3) Dependability, and 4) Confirmability. The results of this study indicate: 1) positioning strategy: on the customer (customer); on internal capabilities and strengths (company); over competitors (competitors); on changes (change); be a power of differentiation (clarity); compete for the products owned (consistency); have high credibility (credibility), and have superior products (competitiveness). 2) differentiation strategy: unique and different performance and design (product differentiation); friendly service with speed and convenience (service differentiation); capabilities in distribution channels (channel differentiation); Reliable Human Resources (HR) (people differentiation); courage to act (progressive differentiation); Iduka curriculum is always updated (content), industrial cooperation (context), and technology with other facilities (infrastructure: inabler) 3) branding strategy; innovative (core identity); open (extended identity); public trust (value proposition). 4) Positioning-Differentiation-Brand (PDB) management and reconstruction. Keywords: Education Management, Positioning-Differentiation-Brand (PDB), Educational Progress. The findings of this study are the reconstruction of the education management concept model with the Positioning-Differentiation-Brand (PDB) strategy for the advancement of Islamic education.